2014
DOI: 10.3109/03639045.2014.892958
|View full text |Cite
|
Sign up to set email alerts
|

Novel oleic acid derivatives enhance buccal permeation of didanosine

Abstract: The aim of this study was to explore the potential of novel oleic acid (OA) derivatives as buccal permeation enhancers for the delivery of didanosine (ddI). The OA derivatives, i.e. ester derivative (OA1E), the dicarboxylic acid derivative (OA1A) and the bicephalous dianionic surfactant (OA1ANa) were synthesized and their effects were compared to the parent OA. OA, OA1E, OA1A and OA1ANa at 1% w/w all showed potential for enhancing the buccal permeability of ddI with enhancement ratio (ER) of 1.29, 1.33, 1.01 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 58 publications
2
27
0
Order By: Relevance
“…12,39 All the derivatives synthesized in this study had a higher lipophilicity as compared to their respective parent FA as indicated by the calculated log P values (Table 3). The study further determined the effect of structural modifications to the UFAs via the transformation of carboxylic acid function into a branched tert-butyl ester function on the permeation enhancement efficacy.…”
Section: View Article Onlinementioning
confidence: 77%
See 3 more Smart Citations
“…12,39 All the derivatives synthesized in this study had a higher lipophilicity as compared to their respective parent FA as indicated by the calculated log P values (Table 3). The study further determined the effect of structural modifications to the UFAs via the transformation of carboxylic acid function into a branched tert-butyl ester function on the permeation enhancement efficacy.…”
Section: View Article Onlinementioning
confidence: 77%
“…Although the increases in the permeability parameters by the parent PA were not significantly different from the control, the increases in the permeability parameters by the derivative PA1E 2 were significantly different from the control ( p = 0.0039) ( Table 1). Studies have shown that an increase in enhancer lipophilicity results in an increase in permeation, 12,38,39,63 also possible ionic conjugation between basic dendritic derivatives and the acidic drug could aid in the movement of the TNF across the epidermis of the skin. 4).…”
Section: View Article Onlinementioning
confidence: 99%
See 2 more Smart Citations
“…Owing to toxicity, reduced efficacy and inconvenient dosing requirements, the WHO has recommended the replacement of ddI by another NRTI, lamivudine [21]. At the same time, it still represents a therapeutic alternative in the poorest countries hit by the scourge [22] and an excellent model drug for the investigation of novel drug delivery systems and production processes [23,24].…”
Section: Introductionmentioning
confidence: 99%